A game-theoretical analysis of poliomyelitis vaccination. (21st August 2020) - Cheng, Emily; Gambhirrao, Neeha; Patel, Rohani; Zhowandai, Aufia; Rychtář, Jan; Taylor, Dewey
Highlights: We incorporate the vaccination in a two age-class model of polio dynamics. We perform game theoretical analysis and compare the herd immunity vaccination levels with the Nash equilibrium vaccination levels. We show that the gap between two vaccination levels is too large and the mandatory vaccination policy is therefore needed to achieve a complete eradication. The results are not sensitive to parameter perturbations. Abstract: Poliomyelitis is a worldwide disease that has nearly been eradicated thanks to the Global Polio Eradication Initiative. Nevertheless, the disease is currently still endemic in three countries. In this paper, we incorporate the vaccination in a two age-class model of polio dynamics. Our main objective is to see whether mandatory vaccination policy is needed or if polio could be almost eradicated by a voluntary vaccination. We perform game theoretical analysis and compare the herd immunity vaccination levels with the Nash equilibrium vaccination levels. We show that the gap between two vaccination levels is too large. We conclude that the mandatory vaccination policy is therefore needed to achieve a complete eradication.